The Impact of Formal Education, Specialized Training, and Offense Type on Perceptions of Employability: Can Bias Toward Hiring a Person With a Criminal History Be Mitigated? - Standridge, Rheanna L. (International journal of offender therapy and comparative criminology, 2026)
Though hesitations to hire formerly incarcerated individuals are often related to assumptions about a person’s dangerousness, there remain legitimate reasons, such as limited formal education and basic skills, that prevent returning residents from finding work. Previous research suggests that hiring decisions are confounded by offense type, even if an employer would otherwise consider a person with a criminal history. Thus, it is unclear whether returning residents’ level of education or training can mitigate barriers related to their offense history. Using hypothetical case vignettes of a formerly incarcerated job applicant, this study examined whether hiring decisions were influenced by education and offense type. A between-subjects design with a sample of 223 individuals recruited via MTurk was conducted. Results of this study were largely consistent with prior research suggesting that criminal history presents an obstacle when trying to obtain employment. Implications and future directions are provided in the discussion.